PENILAIAN TINGKAT KESEHATAN BANK PADA PT. BANK PEMBANGUNAN DAERAH BALI DENGAN ANALISIS RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNING, CAPITAL - Purnama Sari, Ni Kadek Ita (E-Jurnal Akuntansi, 2014)
Bank Indonesia issued new regulations with 13/1/PBI/2011 number of banks on the Rating of Public Health ) . The factors assessed were risk profile , good corporate governance , Profitability , and Capital . Regional development banks have the uniqueness of Bali , which has a captive funding , which is owned by its largest shareholder Pemprov.Bali. This study was conducted with the aim to determine the soundness of a bank in PT Bank BPD Bali in 2011 with RGEC analysis and comparative descriptive data analysis techniques. Based on the assessment of credit risk, including "low moderate", it means the portfolio to fund most of the credit exposure is low, provision of funds for better diversification. In other words, the funds available are of good quality or relatively stable business model. Market risk is "low moderate", because the business activities carried out is likely to face a loss of market risk is low for a specified period in the future. Liquidity risk includes "low", this is a very capable terlihatdari BPD bank obligations. Operational risk "moderate", in this case the BPD Bali has a policy, the right to avoid or result in failure or loss and ensure the implementation of appropriate new business opportunities under the control of the management of risk. Legal risk "low", caused by BPD Bali banks have been able to minimize the weaknesses of the agreement and fraud by employees who become legal problems the last few years. Strategic risk management includes "low moderate", because the Bank's low-risk strategy, but with a rising trend, product / banking activities are not classified as complex and diversified. Compliance risk "low moderate", this is reflected by a pretty good track record of compliance. Reputational risks classified as "low moderate", due to the influence of negative reputation of the owner of the Bank and companies associated with small -scale effect and can be handled well. Good self-assessment against the assessment Corpororate Governanace are good    enough". The ratio of earnings to use Return on Assets ( ROA ) of 3.41 % was obtained classified as " healthy " . ROA 66.08 %, classified as "healthy enough". Ratings on Capital using CAR (Capital Adequacy Ratio of 11.83 % was obtained classified as" healthy"
Keywords: BPD; Penilaian tingkat kesehatan bank; Risk Profile; Good Corporate Governance; Earning; Capital